Fifty Years of Dazzling, Dizzying Threads: Anniversary of Pittsburgh Pirates Debuting Double-Knits July 1970. - Moon, Ken (Advances in Social Sciences Research Journal, 2020)
This article was originally accepted for presentation at the Baseball in Literature and Culture Conference at Ottawa University in Ottawa, Kansas, in April 2020 (conference cancelled due to Covid-19 outbreak) and presented virtually (via Zoom) for the 37th Sports Literature Association Conference, Virtual Edition June 19, 2020. This article commemorates the fiftieth anniversary of the Pittsburgh Pirates, when debuting in Three Rivers Stadium fifty years ago July 16, 1970, making a fashion statement in their new uniforms that would change the look of the game as much as the multi-purpose stadiums and artificial surface fields Major Leaguers played on. Their white double-knit uniforms would spark a revolution in uniform design soon to be adopted by all the Major League teams within a couple years. Their uniform’s nylon-cotton blend fabric changed the look of Major League Baseball at a time when advancements in textile technology combined with a freer spirit in graphics experimentation allowed for bold—and sometimes wild—fashion designs not seen before in professional sports. Several books along with news and commercial web sites/sources are referenced to confirm information in the article.